Criminal Act of Contempt Through Electronic Information Media - I Nyoman Putu Budiartha; I Made Minggu Widyantara; I Nengah Nuarta (Fakultas Hukum, Universitas Warmadewa, 2018)
The rapid current of globalization raises many problems in almost all aspects of human life, covering the political, social, cultural, economic, scientific and technological fields, so that fundamental changes in people's habits arise predominantly. Following the issuance of Law Number 11 Year 2008 on Electronic Information and Transactions (ITE) that was amended to Law Number 19 Year 2016 regarding the Amendment of Law Number 11 Year 2008 regarding Information and Electronic Transactions, many polemics and cases that lead to the pros and cons of the articles in the ITE Law took place. This study examines the classification of an offense of criminal act of contempt committed through electronic information media of and reveals the legal standing for such kind a criminal act. This study was conducted using normative method through analysis of legal interpretation and descriptive analysis. Apparently, the results confirm that the element of